Efficacy of Systemic Vitamin C Supplementation in Reducing Corneal Opacity Resulting from Infectious Keratitis - Cho, Yong-Wun (Medicine (Baltimore), 2014)
The objective of this study was to determine the effect of vitamin C supplementation on reducing the size of corneal opacity resulting from infectious keratitis. The study included 82 patients (82 affected eyes), admitted for infectious keratitis from January 2009 to August 2013, who were followed for more than 3 months. Patients were divided into control, oral vitamin C (3 g/d), and intravenous vitamin C (20 g/d) groups during hospitalization. Corneal opacity sizes were measured using anterior segment photographs and Image J program (version 1.27; National Institutes of Health, Jinju, South Korea) at admission, discharge, and final follow-up. The corneal opacity size used for analysis was the measured opacity size divided by the size of the whole cornea. The corneal opacity size decreased by 0.03 ± 0.10 in the oral vitamin C group, 0.07 ± 0.22 in the intravenous vitamin C group, and 0.02 ± 0.15 in the control group. Intravenous vitamin C reduced the corneal opacity size more than oral vitamin C (P = 0.043). Intravenous vitamin C produced greater reduction in corneal opacity size in younger patients (P = 0.015) and those with a hypopyon (P = 0.036). Systemic vitamin C supplementation reduced the size of corneal opacity resulting from infectious keratitis. Intravenous vitamin C was more beneficial than oral supplementation, especially in younger patients and those with hypopyon.